Influence of feed type on egg production of Tswana laying Chicken - Aganga, A.A.; Tshwenyane, S.O.; Molefhe, L. (Science Alert, 2003)
The experiment was done at estate management unit in Sebele, Gaborne. Ten 23 weeks old laying Tswana chickens were bought from a local farmer and divided into two groups of five each, using complete randomised design. Group one was fed on layer mash and the other group was fed on composite local feed which was a mixture of sorghum, maize and sunflower traditionally used as a supplementary feed under free range system in Botswana. All layers were dewormed using piperazine and treated with oxytetrazine to present disease. 250g of feed and 200ml of water were provided ad-libitum. The layers were individually caged to monitor daily feed and water intake. Collection and weighing of eggs were done every day for 90 days. Tswana layers fed on layers mash produced on average five eggs per week while those on composite local feed produced one egg per week that is 400% more production on layers compared to local supplementary feed.